2022
DOI: 10.29303/jku.v11i2.763
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Type 2 Diabetes Mellitus: Role in Insulin Resistance, Glycemic Control and Long Term Complications

Abstract: Vitamin D has a number of roles in various body systems with receptors scattered in many organs,1,2 showing a link between vitamin D and several chronic diseases such as cancer, diabetes and autoimmune disease.3,4 Several studies have shown the role of vitamin D in type 2 diabetes in controlling blood sugar levels and HbA1c levels. Vitamin D plays a role in increasing insulin sensitivity and secretion and suppressing inflammation in type 2 diabetes. Vitamin D has a protective role in various complications of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…These findings are supported by numerous reports that have shown a higher risk of developing diabetes in individuals with VDD [22,23]. VD can play significant roles in improving glucose metabolism and IR in DM by enhancing secretion and sensitivity of insulin, as well as mitigating inflammation in T2DM [24]. VDD has been linked to poor glycemic control and IR in patients with T2DM, as well as complications of DM [25].…”
Section: Discussionsupporting
confidence: 70%
“…These findings are supported by numerous reports that have shown a higher risk of developing diabetes in individuals with VDD [22,23]. VD can play significant roles in improving glucose metabolism and IR in DM by enhancing secretion and sensitivity of insulin, as well as mitigating inflammation in T2DM [24]. VDD has been linked to poor glycemic control and IR in patients with T2DM, as well as complications of DM [25].…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have indicated that vitamin D inhibits the formation of free radicals and plays a crucial part in the functioning of pancreatic β-cells, insulin sensitivity, as well as secretion through direct or indirect mechanisms. 13 Vitamin D supplementation is an approach to meeting the required nutrients in patients with diabetes mellitus. Vitamin D has the ability to enhance insulin sensitivity by directly interacting with receptors, thereby facilitating glucose transport across cells and activating peroxisome proliferator-activated receptor D. Additionally, it stimulates insulin secretion through direct interaction with vitamin D receptors on β cells and indirectly regulating calcium transport within β cells.…”
Section: Resultsmentioning
confidence: 99%